Detention: problems of criminal procedural regulation and solutions - Фариник, В.І (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2016)
Features of Criminal Procedure detention. The problems of criminal procedural regulation detention and the necessity of amending the Code of Ukraine. Criminal procedural law does not clearly define the goals of detention. However, detention only to ascertain the involvement of a person to commit a crime and the question of application of a preventive measure in the absence of a desire to escape the suspect, continue criminal activity or hide (destroy) the evidence is not entirely justified – because these issues can be addressed and delaying identity, personal information and whose whereabouts are known to the investigating body. The author states that the application of the provisions of the CPC of Ukraine should be aware that each of the institutions which it is fixed, is a definite purpose and procedural order that distinguishes it from other institutions. Therefore, the substitution of certain proceedings contrary to the objective of the criminal proceedings and can not be justified. It is noted that despite the positive experience in implementing measures to ensure the criminal proceedings, the problem of the application of criminal procedural detention remains unresolved and requires quality of legislative proposals that would take into account both the research component, and the problem of enforcement.

Охарактеризовано особливості кримінального процесуального затримання особи. Визначено проблеми кримінальної процесуальної регламентації затримання та обґрунтовано необхідність внесення змін до КПК України.
ЗАТРИМАННЯ ОСОБИ: ПРОБЛЕМИ КРИМІНАЛЬНОЇ ПРОЦЕСУАЛЬНОЇ РЕГЛАМЕНТАЦІЇ ТА ШЛЯХИ ЇХ ВИРІШЕННЯ
Keywords: detention authorized officer; lawful detention; permit detention in order to drive the investigator; затримання; законне затримання; дозвіл на затримання з метою приводу; слідчий